Economic Rhetoric in the Thought of John Paul II - Ciborowski Robert; Kargol-Wasiluk Aneta; Zalesko Marian (Studies in Logic, Grammar and Rhetoric)
The aim of the article is to present the way of economic thinking particularly visible in the social teaching of the Church of John Paul II, through the prism of rhetoric and economic discourse. The authors use the method of analysis and synthesis, focusing on a man being at the center of economic activity. The paper shows the sensitivity of the great twentieth-century thinker to economic matters. His thought could be an inspiration for creating and implementing the concept of economic and social policy and then it would be able to constitute a huge potential of guidelines for a better understanding of the functioning of the modern world and building and implementing solutions that can have an impact on improving the human condition.